1991
DOI: 10.1093/ajcn/53.2.537
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic acid prevents the dose-dependent inhibitory effects of polyphenols and phytates on nonheme-iron absorption

Abstract: The effects of maize-bran phytate and of a polyphenol (tannic acid) on iron absorption from a white-bread meal were tested in 199 subjects. The phytate content was varied by adding different concentrations of phytate-free and ordinary maize bran. Iron absorption decreased progressively when maize bran containing increasing amounts of phytate phosphorous (phytate P) (from 10 to 58 mg) was given. The inhibitory effect was overcome by 30 mg ascorbic acid. The inhibitory effects of tannic acid (from 12 to 55 mg) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
165
2
8

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(179 citation statements)
references
References 25 publications
4
165
2
8
Order By: Relevance
“…The phytate:iron molar ratios greater than 0.15 regarded as indicative of poor iron bioavailability (Siegenberg et al 1991). This result indicated that, the phytate:iron molar ratios of all the accessions are less than the critical value, which implies the absorption of iron all the accessions not inhibited by phytate and as a result the bioavailability of iron is good.…”
Section: Molar Ratios and Bioavailability Of Mineralsmentioning
confidence: 90%
“…The phytate:iron molar ratios greater than 0.15 regarded as indicative of poor iron bioavailability (Siegenberg et al 1991). This result indicated that, the phytate:iron molar ratios of all the accessions are less than the critical value, which implies the absorption of iron all the accessions not inhibited by phytate and as a result the bioavailability of iron is good.…”
Section: Molar Ratios and Bioavailability Of Mineralsmentioning
confidence: 90%
“…For example, ascorbic acid can partially counteract the negative effect of phytic acid and polyphenols on non-haem iron absorption, especially when their levels are low (Hallberg et al, 1989;Siegenberg et al, 1991). Hence, although breastmilk alone is suf®cient to ful®ll the ascorbic acid needs of breast-fed infants, the addition of vitamin-C containing foods to plant-based complementary foods should always be encouraged.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that lactic acid fermentation increased the utilisation of iron from food by breakaway of inorganic iron from complex substances under the influence of vitamin C (SIEGENBERG 1991;VENKATESH 1998).…”
Section: Nutritional Aspects Of Lactic Acid Fermentationmentioning
confidence: 99%
“…Food fermentations that increase the protein content or improve the balance of essential amino acids or their availability will have a direct curative effect. Similarly fermentations that increase the content or availability of vitamins such as thiamine, riboflavin, niacin or folic acid can have profound direct effects on the health of the consumers of such foods (STEINKRAUS 1997).It was shown that lactic acid fermentation increased the utilisation of iron from food by breakaway of inorganic iron from complex substances under the influence of vitamin C (SIEGENBERG 1991;VENKATESH 1998).Fermentation may reduce the content of non-digestible material in plant foods such as cellulose, hemicellulose and polygalacturonic and glucuronic acids. Breakdown of these compounds may lead to the improved bioavailability of mineral and trace elements (KALANTZOPOULOS 1997).…”
mentioning
confidence: 99%